Pengaruh Leverage Dan Profitabilitas Terhadap Tax Avoidance Dimoderasi Oleh Corporate Social Responsibility: Studi Empris pada Perusahaan Manufaktur yang terdaftar di LQ45 2017-2020 - zanra, sri (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2022)
This study aims to determine the effect of Leverage, and Profitability on Tax avoidance with Corporate social responsibility as a moderating variable (empirical study on manufacturing companies listed in LQ45 in 2018-2020). The data used in this study is secondary data from the annual reports of companies that listed on LQ45 on the Indonesia Stock Exchange. The method used in this research is multiple linear regression analysis method and moderated regression analysis. The sample selection in this study was using the purposive sampling method in which a sample of 24 companies was obtained with a total of 96 observations for 4 years of observation (2017-2020). The results of this study indicate that the profitability variable has an effect on tax avoidance. Leverage, profitability and Corporate social responsibility variables can explain the tax avoidance variable by 53.1%. The results of this study also show that Corporate social responsibility is able to moderate the effect of leverage on Tax avoidance but is not able to moderate the profitability of Tax avoidance .